On abundance, phenology and natural history of Geophilomorpha from a mixedwater inundation forest in Central Amazonia (Chilopoda) - de Morais, José Wellington (1997)
Fil: de Morais, José Wellington. Instituto Nacional de Pesquisas da Amazonia (INPA); Brazil